Low-grade inflammation and inflammatory mediators in individuals with prediabetes - Marinković, Dejan M.; Dragović, Tamara; Stanojević, Ivan; Djurić, Predrag V.; Dejanović, Bratislav; Rakočević, Jelena; Kiković, Saša; Malović, Dragana; Stevanović, Ivana; Ristić, Petar; Petrović, Marijana; Hajduković, Zoran Lj. (Vojnosanitetski pregled, 2024)
Background/Aim. Prediabetes is a condition that refers to the state of hyperglycemia not sufficiently high to reach the diagnostic values for type 2 diabetes mellitus (T2DM). This condition often precedes the appearance of T2DM. The association between the development of early glycoregulation disorders and the state of low-grade chronic inflammation is still not sufficiently well understood. The aim of the study was to assess the values of different inflammatory mediators and biomarkers in individuals with prediabetes. Methods. This cross-sectional, observational study included 60 respondents divided into two groups: the prediabetes group (PDG) with 31 patients and the healthy control group (HCG) with 29 respondents.  Serum values of seven selected cytokines/biomarkers were compared between the two groups. Examined biomarkers were: interleukin (IL)-1β, IL-6, IL-8, IL-18, tumor necrosis factor (TNF)-α, E-selectin, and vascular endothelial growth factor (VEGF)-A. In addition, the values of body mass index (BMI), waist circumference (WC), blood pressure (BP), serum triglyceride (TG), fasting plasma glucose (FPG), and glycated hemoglobin (HbA1c) were also compared between the two groups. Results. PDG patients had statistically significantly higher TNF-α values compared to the HCG patients (73 pg/mL vs. 55 pg/mL, p = 0.024). A trend towards higher levels of IL-8 and IL-1β and lower levels of E-selectin, VEGF-A, and IL-18 was registered in PDG patients but without statistical significance. Furthermore, PDG patients had higher values of BMI, WC, systolic BP, serum TG, FPG, and HbA1c when compared to HCG. Conclusion. The results of our study suggest the importance of inflammation and some inflammatory mediators in the pathogenesis of early glycoregulation disorder. We believe that the main goal of future studies should focus on anti-inflammatory therapy in prediabetes.
Keywords: biomarkers; blood glucose; diabetes mellitus, type 2; prediabetic state.